2013
DOI: 10.1177/1071100713477619
|View full text |Cite
|
Sign up to set email alerts
|

Safety Area for Proximal Metatarsal Procedures

Abstract: The study provides information of normal location and variation of deep plantar artery is which related to medial midfoot complex. This information may be used during proximal metatarsal procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…In this study, the shortest distance from the deep plantar arch to the second, third, and fourth metatarsals in the axial plane was 0.5 mm, 2.2 mm, and 2.8 mm, respectively. Other reports have focused on the deep plantar artery, which is the deep branch of the dorsalis pedis artery [ 17 , 22 ]. Consistent with the findings of those studies, we found that the deep plantar artery ran close to the medial side of the second metatarsal and connected with the dorsalis pedis artery to form the deep plantar arch.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the shortest distance from the deep plantar arch to the second, third, and fourth metatarsals in the axial plane was 0.5 mm, 2.2 mm, and 2.8 mm, respectively. Other reports have focused on the deep plantar artery, which is the deep branch of the dorsalis pedis artery [ 17 , 22 ]. Consistent with the findings of those studies, we found that the deep plantar artery ran close to the medial side of the second metatarsal and connected with the dorsalis pedis artery to form the deep plantar arch.…”
Section: Discussionmentioning
confidence: 99%
“…Proximal metatarsal osteotomies are very effective for correcting forefoot deformities because they allow precise control of the shortening and elevation of the metatarsal head [ 15 , 16 ]. However, surgery that involves the lesser metatarsals can lead to iatrogenic disruption of the blood supply to the metatarsals and adjacent structures [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Consideration of potential injury to the D-PL artery and the risk for surgical complications related to proximal metatarsal procedures and amputation warrant a closer look at the vascular positional anatomy in this area. Previous studies have investigated the location of the D-PL artery and have provided general guidelines to surgeons 1,2,5 . The present study was therefore undertaken to obtain a more detailed understanding of the anatomical relationship of the D-PL artery to the first metatarsal, with the aim to develop and provide cautionary guidelines to aid surgeons when dissecting in the region of the proximal first intermetatarsal space and for fixation placement.…”
Section: Japma Article In Pressmentioning
confidence: 99%